2019
DOI: 10.1111/joim.12966
|View full text |Cite
|
Sign up to set email alerts
|

The role of diet in irritable bowel syndrome: implications for dietary advice

Abstract: Rej A, Aziz I, Tornblom H, Sanders DS, Simr en M (Royal Hallamshire Hospital, Sheffield

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 78 publications
(127 reference statements)
1
50
0
1
Order By: Relevance
“…Issues with following a low FODMAP diet, as opposed to traditional dietary advice, include the need for a specialist dietitian to implement it, followed by close monitoring to avoid nutritional deficiencies or the development of overly restrictive eating habits. [207][208][209] The latter emphasises the importance of screening out patients at high risk for such behaviour prior to recommending such diets. [207][208][209] This can be achieved using…”
Section: Fibre and Dietary Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues with following a low FODMAP diet, as opposed to traditional dietary advice, include the need for a specialist dietitian to implement it, followed by close monitoring to avoid nutritional deficiencies or the development of overly restrictive eating habits. [207][208][209] The latter emphasises the importance of screening out patients at high risk for such behaviour prior to recommending such diets. [207][208][209] This can be achieved using…”
Section: Fibre and Dietary Therapiesmentioning
confidence: 99%
“…[207][208][209] The latter emphasises the importance of screening out patients at high risk for such behaviour prior to recommending such diets. [207][208][209] This can be achieved using…”
Section: Fibre and Dietary Therapiesmentioning
confidence: 99%
“…The authors voice concerns regarding the effectiveness of dietary therapies for functional bowel disorders. However, several studies demonstrate the growing evidence for the use of traditional dietary advice, low FODMAP diet (LFD) and gluten free diet (GFD) for Irritable bowel syndrome (IBS) [3].…”
mentioning
confidence: 99%
“…We would disagree that the 5Ad protocol is a 'bottom up' approach, but rather a 'top down' approach, as it involves restriction of high FODMAPs and other dietary components. In contrast, a GFD could be viewed as a 'bottom up' approach, through the reduction of fructans, with a response rate of 30-71% to this diet [3]. Recent research demonstrated patients use gluten free products, classed as 'low fructans foods', whilst on the LFD personalisation stage [4].…”
mentioning
confidence: 99%
“…More than one mechanism contributes to the development of IBS [13]. It's known clearly that dysregulation of the autonomic nervous system, maladjustment of the hypothalamic-pituitary-adrenal axis (HPA), increased pain sensitivity, imbalanced gut microbial population, and altered enteric physiology participate in the pathophysiology of IBS [14]. In recent years, extensive attention has also been paid to the roles of inflammation and immunity Table 2 Comparison of CRF masculine neuron of hypothalamus (expressed by x ± s)…”
Section: Discussionmentioning
confidence: 99%